Cassie-to-Wenzel transition of droplet on the superhydrophobic surface caused by light induced evaporation. (5th November 2018) - Chen, Rong; Jiao, Long; Zhu, Xun; Liao, Qiang; Ye, Dingding; Zhang, Biao; Li, Wei; Lei, Yuanpeng; Li, Dongliang
Highlights: Light induced droplet evaporation on the superhydrophobic surface is studied. Rapid transition of the droplet from the Cassie state to Wenzel state is observed. Condensed droplets in the microstructures present the Wenzel state. Coalescence between condensed droplets and original one cause the wetting transition. Dimensionless final migration distances under various conditions are similar. Abstract: The droplet-based open microfluidics, which manipulates the liquid droplets in an open space to accomplish various functions, has attracted ever-increasing attentions all over the world. In recent, the incorporation of the optics into the droplet-based open microfluidics has resulted in new methods for optically manipulating the droplets. Among them, the photothermal effect has shown its distinct potentials in controlling the droplet by the light-caused phase change with unique merits of flexibility, precision, remarkable efficiency and non-contact state. In this work, we studied the droplet evaporation on the textured superhydrophobic surface actuated by the photothermal effect of a focused infrared laser with the wavelength of 1550 nm. The transition of the droplet from the Cassie state to the Wenzel state accompanying with the obvious extension of the triple-phase contact line was observed. It was confirmed that this Cassie-to-Wenzel transition was actuated by the continuous condensation in the microstructures of the superhydrophobic surface and coalescence between the condensed droplets and the original one. The effects of the laser power and the initial droplet volume on the Cassie-to-Wenzel transition and the extension of the triple-phase contact line were investigated. It was found that the final migration distance of the triple-phase contact line was gradually increased with the initial droplet volume. With the increase of the laser power, the extension process was accelerated as a result of the intensified light-caused evaporation. Noticeably, it was demonstrated that the dimensionless final migration distance under different conditions were similar.